Geology at ANU (1959-2009) Fifty years of history and reminiscences - Rickard, Mike; Caton, Judith (ANU Press, 2010)
This history was undertaken to celebrate the 50th anniversary of the Geology Department at ANU, and to honour its founding professor David A. Brown. It includes contributions from some 100 former students outlining their career successes. This history was compiled by Dr Mike Rickard, a staff member of the Department of Geology from 1963 to 1997, who also served as Head of Department for seven years. He graduated BSc and PhD from Imperial College London in 1957 and has specialised in mapping the structure of mountain chains in Ireland, Canada, Norway, and southern South America. He also mapped volcanic rocks for the Geological Survey of Fiji. He taught Structural Geology and Tectonics and has supervised field work in south eastern and central Australia. After retirement he has taught U3A courses in Earth Science.